'Saving' education : religion and/in historically black colleges and universities - Pinn, Anthony B. (Higher education leadership & study of historically black colleges and universities, 2025)
Many assume a connection between historical black colleges and universities (HBCUs) and religion. Yet, the nature and meaning of this relationship has often been overlooked. 'Saving' Education seeks to address this oversight by exploring the impact of theological concerns and the changes resulting from the Reconstruction and Jim/Jane Crow on the ethos of these institutions and their students' worldview. Some of the key questions which guide this exploration include: How have significant figures shaped the educational communities and missions of HBCUs within their socio-cultural, intellectual, and theological contexts? What dynamics of critical thinking are essential in a predominantly Black educational setting, and how do these dynamics influence pedagogy? What role does the university or college chapel play in defining the nature and global presence of HBCUs? Such questions and the considerations inform this slim volume composed of five essays. They also underscore a broader inquiry: How does the complex relationship with religion define the history, mission, and impact of historically Black colleges and universities (HBCUs)? This book delves into both the personal and communal aspects of this theme, offering insights and challenges across various responsibilities assumed by HBCUs, particularly in relation to religious thought and practice. Together, these essays provide a layered, multidisciplinary examination of the influence of religion on the mission and activities of HBCUs over the centuries.